BFFT formalism applied to the minimal chiral Schwinger model - Natividade, C. P.; Boschi-Filho, H.; Belvedere, L. V. (World Scientific Publ Co Pte Ltd, 2004)
We consider the minimal chiral Schwinger model, by embedding the gauge non-invariant formulation into a gauge theory following the Batalin-Fradkin-Fradkina-Tyutin point of view. Within the BFFT procedure, the second-class constraints are converted into strongly involutive first-class ones, leading to an extended gauge-invariant formulation. We also show that, like the standard chiral model, in the minimal chiral model the Wess-Zumino action can be obtained by performing a q-number gauge transformation into the effective gauge non-invariant action.